Topoisomerase 2β and DNA topology during B cell development - Papapietro, Olivier; Nejentsev, Sergey (Frontiers in Immunology, 2022)
Topoisomerase 2β (TOP2B) introduces transient double strand breaks in the DNA helix to remove supercoiling structures and unwind entangled DNA strains. Advances in genomic technologies have enabled the discovery of novel functions for TOP2B in processes such as releasing of the paused RNA polymerase II and maintaining the genome organization through DNA loop domains. Thus, TOP2B can regulate transcription directly by acting on transcription elongation and indirectly by controlling interactions between enhancer and promoter regions through genome folding. The identification of TOP2B mutations in humans unexpectedly revealed a unique role of TOP2B in B-cell progenitors. Here we discuss the functions of TOP2B and the mechanisms leading to the B-cell development defect in patients with TOP2B deficiency.